Gene miaA for post‐transcriptional modification of tRNAXXA is important for morphological and metabolic differentiation in Streptomyces. Issue 1 (6th May 2019) - Koshla, Oksana; Yushchuk, Oleksandr; Ostash, Iryna; Dacyuk, Yuriy; Myronovskyi, Maksym; Jäger, Gunilla; Süssmuth, Roderich D.; Luzhetskyy, Andriy; Byström, Anders; Kirsebom, Leif A.; Ostash, Bohdan
Summary: Members of actinobacterial genus Streptomyces possess a sophisticated life cycle and are the deepest source of bioactive secondary metabolites. Although morphogenesis and secondary metabolism are subject to transcriptional co‐regulation, streptomycetes employ an additional mechanism to initiate the aforementioned processes. This mechanism is based on delayed translation of rare leucyl codon UUA by the only cognate tRNA Leu UAA (encoded by bldA ). The bldA –based genetic switch is an extensively documented example of translational regulation in Streptomyces . Yet, after five decades since the discovery of bldA, factors that shape its function and peculiar conditionality remained elusive. Here we address the hypothesis that post‐transcriptional tRNA modifications play a role in tRNA‐based mechanisms of translational control in Streptomyces . Particularly, we studied two Streptomyces albus J1074 genes, XNR_1074 ( miaA ) and XNR_1078 ( miaB ), encoding tRNA (adenosine(37)‐N6)‐dimethylallyltransferase and tRNA (N6‐isopentenyl adenosine(37)‐C2)‐methylthiotransferase respectively. These enzymes produce, in a sequential manner, a hypermodified ms 2 i 6 A37 residue in most of the A36‐A37‐containing tRNAs. We show that miaB and especially miaA null mutant of S. albus possess altered morphogenesis and secondary metabolism. We provide genetic evidence that miaA deficiency impacts translational level of gene expression, most likely through impaired decoding of codons UXX and UUA in particular. Abstract : In Streptomyces albus J1074, genes XNR_1074 and XNR_1078 encode orthologues of MiaA and MiaB enzymes, respectively, involved in post‐transcriptional modification of nucleoside residue A37 of tRNAXXA . Deletion of miaA impaired production of antibiotics and morphogenesis, most likely because of less efficient decoding of codons UXX, including UUA.